The Lived Experience of Crossing the Road When You Have Developmental Coordination Disorder (DCD): The Perspectives of Parents of Children With DCD and Adults With DCD - Wilmut, Kate; Purcell, Catherine (Frontiers in Psychology, 2020)
Pedestrians are one of the most vulnerable groups at the roadside, furthermore, previous research has demonstrated perceptual-motor limitations in individuals with DCD which may put these individuals at even more at risk in the context of road crossing. However, it is unclear whether this is the lived experience of these individuals at the roadside. Furthermore, difficulties with road crossing and safety have been found in other neurodevelopmental disorders but the impact this might have on an individual with co-occurring difficulties is unknown. Therefore, we utilised a questionnaire to survey the lived experience of adults with DCD and parents of children with DCD with the specific objectives of describing behaviours exhibited by adults and children with DCD (the latter reported by parents) at the roadside and to determine the how these individuals perceive road crossing actions. For each of these we compared different co-occurrence groups. We also had one final objective which was not focussed on road crossing but more on the general perception of accidents and unrealistic optimism. Individuals with co-occurrences which have previously been linked to unsafe crossing behaviours (i.e. ADHD, ASD and LD) reported a greater regularity of dangerous looking behaviour (forgetting to look, running without looking) and visibility (crossing between cars, crossing when you can’t see), these adults and the parents of these children were seemingly aware of the risky nature of these behaviours. When asked ‘why’ crossing ability might be different, perceptual and motor difficulties alongside heightened awareness of risk and lowered awareness of risk were all cited by participants. Unrealistic optimism was not an explanation for the risky behaviour in adults with DCD and in fact, these adults demonstrated a clear understanding of the likelihood of accidents. The findings of this study suggest that road crossing is perceived to be more challenging for both children and adults with DCD and this needs to be taken into account when considering remediation for this group.